THE EFFECT OF PRICE DISCOUNT AND IN-STORE DISPLAY ON IMPULSE BUYING - noor, zulki zulkifli (Universitas Padjadjaran, 2020)
This study aims to determine the effect on the Impulse Buying Discount Price on Borma Departement Store Bandung, determine the effect of In-Store Display on Borma Departement Store Impulse Buying in Bandung, and determine the influence of Price Discount and In-Store Display on Borma Departement Store Impulse Buying in Bandung. The methodology used is a descriptive quantitative method, the unit of analysis in this study is Borma Departement Store Terrain and observation units are customers of Borma Departement Store Terrain much as 980 respondents. Mechanical determination of the number of samples used in this study is the systematic randomsampling and the sample size is 91 respondents. The method used the techniques of collecting data through library research and field research conducted systematically based on objective research. The analytical method used to solve problems and prove the hypothesis is descriptive analysis. The finding are price discount has a positive and significant impact on the Impulse Buying.In-Store Display partially has a positive and significant impact on the Impulse Buying.Price Discount and In-Store Display simultaneously have a positive influence on Impulse Buying..